2001
DOI: 10.1093/ndt/16.6.1239
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled parallel‐group trial on efficacy and safety of iron sucrose (Venofer®) vs iron gluconate (Ferrlecit®) in haemodialysis patients treated with rHuEpo

Abstract: High doses of iron sucrose (Venofer((R)) at a dose of 250 mg/month) was equally effective in maintaining haemoglobin and equally well tolerated as low doses of iron gluconate (Ferrlecit((R)) at a dose of 62.5 mg once per week) in stable, rHuEpo treated haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 14 publications
0
53
0
6
Order By: Relevance
“…In contrast to the above findings, several studies concluded that there was no increased infection rate resulting from iron therapy in patients without renal failure or in patients undergoing dialysis (41)(42)(43). Furthermore, in a study that compared effectiveness and safety of iron sucrose and iron gluconate, no difference was observed between these iron complexes (44).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to the above findings, several studies concluded that there was no increased infection rate resulting from iron therapy in patients without renal failure or in patients undergoing dialysis (41)(42)(43). Furthermore, in a study that compared effectiveness and safety of iron sucrose and iron gluconate, no difference was observed between these iron complexes (44).…”
Section: Discussionmentioning
confidence: 94%
“…The low frequency of side effects of iron gluconate and particularly iron sucrose was mentioned in previous trials [7,8]. Nevertheless, higher doses of iron gluconate caused complications such as chills, severe vomiting, hypotension, and syncope [9].…”
Section: Discussionmentioning
confidence: 93%
“…Despite study shortcomings and lack of definitive randomized trials, the iron sucrose Venofer and the iron gluconate Ferrlecit are believed to have lower risks of serious anaphylactic-type reactions than the iron dextrans [20][21][22][23][24][25][26][27] possibly because they do not initiate an anti-dextran response [25]. A stated advantage of iron dextran, besides lower cost, is the ability to infuse a patient's total iron requirement in one administration (total dose infusion) [28][29][30] so clinicians can conveniently treat patients in a single hospital or clinic visit.…”
Section: Discussionmentioning
confidence: 99%